Systematic review of strengths and limitations of Randomized Controlled Trials for non-pharmacological interventions in mild cognitive impairment: Focus on Alzheimer's disease - Tara Horr; Barbara J. Messinger‐Rapport; Jagan A. Pillai (2014)
Non-pharmacological interventions may improve cognition and quality of life, reduce disruptive behaviors, slow progression from Mild Cognitive Impairment (MCI) to dementia, and delay institutionalization. It is important to look at their trial designs as well as outcomes to understand the state of the evidence supporting non-pharmacological interventions in Alzheimer's disease (AD). An analysis of trial design strengths and limitations may help researchers clarify treatment effect and design future studies of non-pharmacological interventions for MCI related to AD.